Characterization of the Nicotianamine Exporter ENA1 in Rice - Nozoye, Tomoko; von Wirén, Nicolaus; Sato, Yoshikatsu; Higashiyama, Tetsuya; Nakanishi, Hiromi; Nishizawa, Naoko K. (Frontiers in Plant Science, 2019)
Under iron (Fe) deficiency, graminaceous plants produce and secrete Fe-chelating phytosiderophores of the mugineic acid family (MAs) into the rhizosphere to solubilize and mediate uptake of sparingly soluble Fe in the soil. MAs and their biosynthetic intermediate, nicotianamine (NA), are also important for the translocation of divalent metals such as Fe and zinc (Zn) throughout the plant body. In this study, the physiological role of the efflux transporter ENA1, which exports NA out of cells, was analyzed in rice. Promoter-GUS analysis showed that ENA1 was mainly expressed in roots, and strongly upregulated under Fe-deficient conditions. In epidermal onion cells and rice roots, GFP-tagged ENA1 localized mainly to the plasma membrane, while a part of the fluorescence was observed in vesicular structures in the cytoplasm. In the younger stage after germination, ENA1-overexpressing rice plants exhibited truncated roots with many root hairs compared to wild-type plants, while these phenotype were not observed in high Zn-containing medium. In Arabidopsis, which use a different strategy for Fe uptake from rice, ENA1 overexpression did not show any apparent phenotypes. Oligo DNA microarray analysis in rice showed that ENA1 knockout affects the response to stress, especially in root plastids. These results suggest that ENA1 might be recycling between the plasma membrane and cellular compartments by vesicular transport, playing an important role in the transport of NA, which is important for the physiological response to Fe deficiency.